Empirical Test of Tax Ratio: (Empirical Studies in ASEAN 2011-2017) - Wulandari, Rosita; Syafrizal, Syafrizal; Mubarok, Ali (Jurnal Riset Akuntansi dan Keuangan, 2020)
The purpose of this study is to show the effect of per capita income, and economic structure on tax ratios in ASEAN countries for the period 2011-2017. This study uses data sourced from the official website of the World Bank. The population of this study is data on the amount of tax revenue, GDP, GDP per sector, and economic structure. The sample is taken from time series data on the amount of tax revenue, GDP, GDP per sector, tax rates, and economic structure in ASEAN countries for 7 years from 2011-2017. The method used in determining the sample is a purposive sampling method that is sampling based on certain criteria that have been determined by researchers. The sample obtained in this study amounted to 8 countries in ASEAN. The data analysis method used in this study is panel data regression analysis. Based on the results of research conducted, the partial test results obtained indicate that income per capita, and economic structure affect the tax ratio. Simultaneous test results in this study also indicate per capita income, and economic structure have an influence on tax ratios in ASEAN countries 2011-2017.